2008
DOI: 10.1016/j.bbagrm.2007.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of substrate specificity in RNA-dependent nucleotidyl transferases

Abstract: Poly(A) polymerases were identified almost fifty years ago as enzymes that add multiple AMP residues to the 3′ ends of primer RNAs without use of a template from ATP as cosubstrate and with release of pyrophosphate. Based on sequence homology of a signature motif in the catalytic domain, poly(A) polymerases were later found to belong to a superfamily of nucleotidyl transferases acting on a very diverse array of substrates. Enzymes belonging to the superfamily can add from single nucleotides of AMP, CMP or UMP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 70 publications
(126 reference statements)
1
20
0
Order By: Relevance
“…It should be noted that CCA transferase (CCAtr) activity in several organisms such as Synechocystis sp., Deinococcus radiodurans and Aquifex aeolicus is split between two enzymes, one that adds -CC and the other that adds a terminal -A (Tomita and Weiner, 2002). Although it is difficult to assign an activity to a Class II NTR based on primary sequence, several informatic and experimental approaches (Betat et al, 2004;Cho et al, 2007;Martin and Keller, 2007;Martin et al, 2008) identified Glu193 in Bacillus stearothermophilus as a residue in the PAP domain that allows discrimination between CCAtrs and PAPs. In CCAtrs this residue is Glu, but is variable in other family members.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that CCA transferase (CCAtr) activity in several organisms such as Synechocystis sp., Deinococcus radiodurans and Aquifex aeolicus is split between two enzymes, one that adds -CC and the other that adds a terminal -A (Tomita and Weiner, 2002). Although it is difficult to assign an activity to a Class II NTR based on primary sequence, several informatic and experimental approaches (Betat et al, 2004;Cho et al, 2007;Martin and Keller, 2007;Martin et al, 2008) identified Glu193 in Bacillus stearothermophilus as a residue in the PAP domain that allows discrimination between CCAtrs and PAPs. In CCAtrs this residue is Glu, but is variable in other family members.…”
Section: Resultsmentioning
confidence: 99%
“…The sidewalls of the cleft are lined by the β-sheet of the catalytic domain and by helices α5-α6 of the central domain, whereas helix α4 lines the bottom. The cleft harbors the active site: Strands β2 and β5 of the catalytic domain provide the three conserved aspartic acids that mediate the chemical reaction characteristic of nucleotidyl transferases (25,35) (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Trf4p/5p belongs to a family of ribonucleotide transferases in the Pol ß superfamily of nucleotidyl transferases (10,11). It consists of N-and C-terminal sequences that have little predicted secondary structure, a catalytic domain similar in sequence to several Pol ß members with known structures, and an adjacent "central domain," which shares a short nucleotide recognition motif hx(I/L/V)(E/Q)(E/D/N)PhxxxxNxx (h, hydrophobic; x, any residue) with so-called noncanonical Pol β RNA polymerases.…”
mentioning
confidence: 99%